Psychosocial distress and utilization of professional psychological care in cancer patients: An observational study in National Comprehensive Cancer Centers (CCCs) in Germany. Issue 12 (19th October 2018) - Weis, Joachim; Hönig, Klaus; Bergelt, Corinna; Faller, Hermann; Brechtel, Anette; Hornemann, Beate; Stein, Barbara; Teufel, Martin; Goerling, Ute; Erim, Yesim; Geiser, Franziska; Niecke, Alexander; et al.
Abstract: Objective: The study aimed to assess cancer patients' use of psychological care and its correlates in a large sample of cancer patients in Comprehensive Cancer Centers (CCCs) in Germany. Methods: In a multicenter study in Germany, cancer patients with various diagnoses were evaluated for self‐reported use of psychological support. We measured psychological distress, depression and anxiety, quality of life, and social support with standardized questionnaires and analyzed its association with the utilization of psychological care using multivariable logistic regression. This paper focuses on a cross‐sectional analysis of the data assessed during inpatient care. Results: Three thousand fifty‐four (50%) of hospitalized patients were asked for participation, and n = 1632 (53.6%) participated. We were able to analyze n = 1, 398 (45.9%) patients. Three hundred ninety‐seven (28.4%) of the sample utilized psychological support. Users of psychological care were significantly younger than nonusers (odds ratio [OR]: 0.967, P  < 0.001) and were more often female (OR: 1.878, P  < 0.001), whereas educational level was not associated with the use of psychological care. In the multivariable analysis, effects on the use of psychological care were observed for Hospital Anxiety and Depression Scale (HADS) anxiety (OR: 1.106, P  = 0.001) and both subscales of the 12‐item Short Form Health Survey (SF‐12) quality of life measure (mental, OR: 0.97, P  = 0.002; physical, OR: 0.97, P  = 0.002). Conclusion: Psychological distress and anxiety are higher, and quality of life is lower in users of psychological care in comparison with nonusers during inpatient cancer treatment. Although psychooncological services should be provided to all patients who need them, special efforts should be made to reach populations that report low utilization.